Adaptive aspects of maximizing in times of COVID-19: coping efforts linking maximization to well-being - Jun, Young Joo; Choi, Incheol; Kim, Joo Hyun (Frontiers in Psychology, 2024)
Introduction: Maximization, which indicates the tendency to make the best choices by thoroughly searching and comparing alternatives, has long been considered a negative correlate of well-being. However, recently, it was proposed that maximizing tendency can lead to better coping efforts in a certain stressful situation and thus could be more adaptive. The present research aimed to discover positive features of maximization by examining the mediation links between maximization and well-being through coping strategies used during the COVID-19 pandemic.Methods: A sample of 3,493 participants responded to an online survey from January 20 to October 11 in 2020 during the COVID-19 pandemic. The 13-item Maximization Scale assessed individuals' maximizing tendency in terms of the maximization index and its three subdimensions (i.e., high standards, alternative search, and decision difficulty). Four coping strategies were used to assess coping efforts during the COVID-19 pandemic (i.e., preventive measures, cognitive appraisal, self-distraction, and social connection). Hedonic and eudaimonic aspects of well-being were measured. We established a mediation model to examine an indirect link between maximization and well-being through the coping strategy and a direct link between maximization and well-being.Results: Path analysis revealed an inconsistent mediation model. There were negative direct associations between maximization measures (i.e., an index and three subdimensions) and wellbeing. However, significant indirect paths were found with varying directions depending on maximization dimensions and coping strategy types. There were five positive indirect associations between the maximization index and well-being via preventive measures, between high standards and well-being through preventive measures and cognitive appraisal, and between alternative search and well-being through self-distraction and social connection. Decision difficulty, however, showed negative indirect relations to well-being through cognitive appraisal, self-distraction, and social connection.Discussion: The current study confirmed the existence of inconsistent mediation effects between maximization and well-being via coping and highlighted coping efforts as one of the positive aspects of maximization. Discussion addressed the double-edged effect of maximization on wellbeing and its beneficial nature in times of distress. Future studies should examine other potential situations and moderators that can delineate maximization's various characteristics with a longitudinal design and samples from diverse backgrounds.